EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK FOCUS GROUP DISCUSSION (FGD) UNTUK MENINGKATKAN KEDISIPLINAN SISWA - Surifa Auwatunnisa; Muqarramah Fitri; Fauzi Aldina (Educandumedia: Jurnal Ilmu pendidikan dan kependidikan, 2024)
This research is based on a preliminary study that the researcher conducted at SMA Negeri 1 Mila, the researcher found several disciplinary violations that were often carried out by students such as being late for school, skipping school hours, and often not attending school. maintain character development in students. This disciplinary issue must be resolved immediately because it has a bad impact on student behavior. Guidance and counseling are solutions that can be taken because the field of work and the approach taken by BK are considered capable of solving the problems that occur. The objectives of the research are: (1) To find out the description of student discipline at SMA N 1 Mila, (2) To find out the description of the implementation of Group Guidance with Focus Group Discussion techniques to improve student discipline at SMA Negeri 1 Mila, (3) To find out how much Most group guidance with Focus Group Discussion (FGD) techniques is effective in improving student discipline at SMA Negeri 1 Mila. This study uses a quantitative approach using a pre-experimental design method of type one group pretestposttest (initial test - single group final test). The population in this study were all second grade students of SMA Negeri 1 Mila, totaling 200 students. The sample in this study were 30 students using random sampling. The instrument used is a Likert scale model. Hypothesis testing using paired sample t-test. Based on the results of the study showed that the value of tcount was 19,458. Then tcount is compared with ttable of freedom df = 29, then the provision of tcount of ttable (19.458 0.68304), the value of sig.(2-tailed) is smaller than the critical value of 0.005 (0.000 0.005), this indicates that H0 is rejected and Ha accepted. Judging from the provisions of tcount > ttable, the calculation result is greater than tcount > ttable. So it can be concluded that group guidance with Focus Group Discussion (FGD) techniques can effectively improve student discipline at SMA Negeri 1 Mila.